Potentials and Limitations of “Input-Output” Analysis (To the 60th Anniversary of Statistical Work in the Field of Intersectoral Research in the CIS Countries) - L. A. Strizhkova; G. O. Kuranov (Мир новой экономики, 2021)
The article reveals the possibilities of using the Russian system of input-output tables and intersectoral models for analytical and forecasting purposes and substantiate managerial decisions in the fild of economic policy. It is shown how the input-output method’s capabilities were implemented at three stages of the development of intersectoral research in Russia, taking into account the specifis of the problems being solved and the development of the statistical base. The primary attention authors paid to the current stage of developing the method and its use directions. A characteristic is given of the constraints objectively inherent in this method and the input-output tables’ information system (IOT). The authors’ position regarding their signifiance is expressed. A new direction in using data from the IOT system is considered — the analysis of the fial product’s cost as accumulated value-added, which implies a full use of the analytical potential of modern input-output tables. Proposals are given for improving the intersectoral toolkit based on taking into account the links between production, the need for investment and the state of the production and technical base.